HUBUNGAN DUKUNGAN SUAMI DENGAN KECEMASAN IBU HAMIL DALAM MENGHADAPI PROSES PERSALINAN - Irma Nurianti; Ika Nur Saputri; Betharia Crisdayanti Sitorus (JURNAL KEBIDANAN KESTRA (JKK), 2021)
Anxiety is an emotional disorder that is often experienced by pregnant women. Anxiety has a negative impact on pregnant women such as stunted fetal growth, weakening uterine muscle contractions, the risk of giving birth to premature babies, and influencing the growth and development of children. Anxiety problems that often occur due to unconformity of the mother's thoughts about the attention she gets that can trigger the level of pain in the mother increases. This study aims to determine the relationship of husband support with the anxiety of pregnant women in dealing with childbirth at the Nining Pelawati Clinic, Kecamatan Lubuk Pakam Kabupaten Deli Serdang in 2020. This type of quantitative research is cross sectional design. The population in sampling uses purpose sampling with a sample size of 20 people. Data collection by questionnaire. Data analysis was performed univariate, bivariate with the Chi-Square test at 95% confidence level, Î± = 5%. The results of the analysis showed that the relationship between husband's support and the anxiety of pregnant women in facing labor at the Nining Pelawati Clinic Kecamatan Lubuk Pakam Kabupaten Deli Serdang in 2020 with a p value of 0.040. It is recommended to the husband to provide support to his wife when she will face labor during pregnancy.